The Leadership Attributes and Commercial Bank Financial Performance: The Mediating Role of Capital Adequacy Ratio - Hien Thu Thi Nguyen (Emerging Science Journal, 2026)
This paper aims to explore how factors such as age, gender, professional qualifications, and experience of the Chairman of the Board of Directors (COB) and Chief Executive Officer (CEO) influence the financial performance of Vietnamese commercial banks. Data are collected from 28 listed banks in Vietnam from 2013 to 2023. The study employs regression methods including OLS, FEM, REM, and FGLS. To ensure robustness and address potential model limitations, SGMM regression is also utilized. The results indicate that banks led by female COBs and CEOs tend to achieve better financial performance. Additionally, older COBs are associated with lower bank performance. The findings also highlight the significant impact of bank leaders' expertise and educational background on financial performance. To the author's knowledge, this is the first study to analyze the combined effect of bank leadership attributes on the profitability of Vietnamese commercial banks within an emerging economy. It is also among the first to examine the mediating role of the capital adequacy ratio (CAR). The results provide a solid basis for stakeholders to make informed decisions related to the recruitment, appointment, training, and development of bank leaders to enhance financial performance.